Viruses of the oral cavity: Prevalence, pathobiology and association with oral diseases - Thakkar, Pari; Banks, Jonathan M.; Rahat, Rani; Brandini, Daniela A. [UNESP]; Naqvi, Afsar R. (Wiley, 2021)
The human oral cavity contains a plethora of habitats and tissue environments, such as teeth, tongue, and gingiva, which are home to a rich microbial flora including bacteria, fungi, and viruses. Given the exposed nature of the mouth, oral tissues constantly encounter infectious agents, forming a complex ecological community. In the past, the discussion of microbiological aspects of oral disease has traditionally focused on bacteria and fungi, but viruses are attracting increasing attention as pathogens in oral inflammatory diseases. Therefore, understanding viral prevalence, pathogenicity, and preference regarding oral tissues is critical to understanding the holistic effects of viruses on oral infections. Recent investigations have demonstrated the abundance of certain viruses in oral inflammatory diseases, suggesting an association between viruses and disease. Human herpesviruses are the most extensively studied viruses in different oral inflammatory diseases. However, challenges in viral detection and the lack of reproducible in vitro and in vivo infection models have limited our progress in understanding viruses and their contribution to oral diseases. This review presents a summary of major mammalian viruses and associated diseases in the human oral cavity. The emergence of a recent pathogen SARS-CoV-2 and its tropism for salivary and periodontal tissues further highlights the relevance of the oral cavity in host-pathogen interaction. Understanding how these different viruses present clinically and influence oral health will advance our understanding of multifactorial oral diseases and their association with viruses.
Keywords: human herpesviruses; inflammation; oral cavity; periodontal disease; viral infection